2015
DOI: 10.1016/j.jppr.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Study of heat transfer and flow of nanofluid in permeable channel in the presence of magnetic field

Abstract: In this paper, laminar fluid flow and heat transfer in channel with permeable walls in the presence of a transverse magnetic field is investigated. Least square method (LSM) for computing approximate solutions of nonlinear differential equations governing the problem. We have tried to show reliability and performance of the present method compared with the numerical method (Runge-Kutta fourth-rate) to solve this problem. The influence of the four dimensionless numbers: the Hartmann number, Reynolds number, Pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Figure 3 shows that increase of magnetic field induction, the temperature value was decreased. While applying B = 0.05 T and B = 1 T the decrease rate is 0.38% and 0.68% according to the B = 0 T. Similar effect of magnetic forces on the flow body temperature was clarified in [3,5,7,8] as temperature increases with increase in the magnetic field intensity Figure 5 presents the variation of local temperature under the influence of applied constant magnetic field B = 1 T and electrical field intensity value are E + = 1e-4 and E -= −1e-4 V/m. While magnetic field is constantly applying on the flow domain with the value is B = 1 T, the local temperature was decreased by the influence of electrical field intensity is E + = 1e-4 V/m.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Figure 3 shows that increase of magnetic field induction, the temperature value was decreased. While applying B = 0.05 T and B = 1 T the decrease rate is 0.38% and 0.68% according to the B = 0 T. Similar effect of magnetic forces on the flow body temperature was clarified in [3,5,7,8] as temperature increases with increase in the magnetic field intensity Figure 5 presents the variation of local temperature under the influence of applied constant magnetic field B = 1 T and electrical field intensity value are E + = 1e-4 and E -= −1e-4 V/m. While magnetic field is constantly applying on the flow domain with the value is B = 1 T, the local temperature was decreased by the influence of electrical field intensity is E + = 1e-4 V/m.…”
Section: Resultssupporting
confidence: 53%
“…It is concluded that heat transfer in channels can be enhanced up to about 75% due to the presence of magnetic field. Fakour et al [3] investigated laminar fluid flow and heat transfer in channel with permeable walls in the presence of a transverse magnetic field. It is concluded that by applied magnetic field, velocity in the channel is reduced and the maximum amount of temperature increases.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting Equations (28) and (29) in Equations (23) and (24) along with boundary conditions (25) and (26), a system of equations is obtained up to first-order as follows.…”
Section: Solution Of the Problemmentioning
confidence: 99%
“…It is noticed that Equation (41) depends upon the P e . The stream function and temperature distributions up to first order can be obtained by substituting zeroth and first-order solutions in Equations (28) and (29).…”
Section: First-order Problem and Solutionmentioning
confidence: 99%
“…They showed that the least square method was more accurate than di erential transformation method. In other analytical investigations, Fakour et al [6,7] employed the least square method to study ow eld and heat transfer in a porous channel in the presence of a transverse magnetic eld. The e ect of thermal radiation on ow eld and heat transfer in a thin liquid lm in a porous medium was investigated by Darzi et al [8] using the least square method.…”
Section: Introductionmentioning
confidence: 99%